2019
DOI: 10.1111/eva.12870
|View full text |Cite
|
Sign up to set email alerts
|

Lack of gene flow between Phytophthora infestans populations of two neighboring countries with the largest potato production

Abstract: Gene flow is an important evolutionary force that enables adaptive responses of plant pathogens in response to changes in the environment and plant disease management strategies. In this study, we made a direct inference concerning gene flow in the Irish famine pathogen Phytophthora infestans between two of its hosts (potato and tomato) as well as between China and India. This was done by comparing sequence characteristics of the eukaryotic translation elongation factor 1 alpha (eEF-1α) gene, generated from 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 81 publications
3
15
0
Order By: Relevance
“…Recently, Wang et al (2020) reported a lack of gene flow between the P . infestans populations in China and India, but the significance of their findings is difficult to interpret as it appears that the populations compared belonged to different clonal lineages and mating types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang et al (2020) reported a lack of gene flow between the P . infestans populations in China and India, but the significance of their findings is difficult to interpret as it appears that the populations compared belonged to different clonal lineages and mating types.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al (2020) reported a lack of gene flow between the P. infestans populations in China and India, but the significance of their findings is difficult to interpret as it appears that the populations compared belonged to different clonal lineages and mating types. A lack of direct gene flow is not unexpected in view of the natural Himalayan barrier, restricted trade in agricultural commodities, and strict border surveillance between these countries.…”
Section: Discussionmentioning
confidence: 99%
“…Preferences of particular isolates to produce either antheridia or oogonia in heterothallic species have been recorded; however, bisexuality is hypothesised in homothallic species [ 29 ], therefore, the possibility of the mating of two isolates of homothallic species cannot be excluded. Outbreeding was documented in either heterothalic P. infestans [ 30 , 31 , 32 ] or P. ramorum [ 33 ], or in homothallic species such as P. sojae and P. porri . In homothallic Phytophthora spp., outbreeding was reported as a possible mechanism generating new pathotypes able to overcome host resistance [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, although there are a low number of amino acid isoforms, as many as 10 nucleotide haplotypes and some reticulation structures were detected in the haplotype network (Figure 2). Intra-gene recombination was not detected in both the current or previous sequences (Wang et al, 2020) in the eEF-1α gene and in the eEF-1α gene the reticulation structures are likely caused by convergent mutations. Intra-gene recombination events have been detected in effector and fungicide target genes of the same pathogen collection (Chen et al, 2018;Yang et al, 2020;Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 77%
“…Strains were purified by three serial transfers of mycelia to fresh rye B media. Details of the pathogen collection and isolation are described in previous publications (Qin et al., 2016; Wang et al., 2020). Only one isolate was secured from each infected leaf and a total of 1,473 isolates were secured from the samples.…”
Section: Methodsmentioning
confidence: 99%